War and Women’s Work : Evidence from the Conflict in Nepal - Menon, Nidhiya; van der Meulen Rodgers, Yana (2012)
This paper examines how Nepal's 1996-2006 civil conflict affected women's decisions to engage in employment. Using three waves of the Nepal Demographic and Health Survey, the authors employ a difference-in-difference approach to identify the impact of war on women's employment decisions. The results indicate that as a result of the Maoist-led insurgency, women's employment probabilities were substantially higher in 2001 and 2006 relative to the outbreak of war in 1996. These employment results also hold for self-employment decisions, and they hold for smaller sub-samples that condition on husband's migration status and women's status as widows or household heads. Numerous robustness checks of the difference-in-difference estimates based on alternative empirical methods provide compelling evidence that women's likelihood of employment increased as a consequence of the conflict.